Better value primary care is needed now more than ever. (10th November 2017) - Watson, Jessica; Salisbury, Chris; Jani, Anant; Gray, Muir; McKinstry, Brian; Rosen, Rebecca
Abstract : Effective primary care is essential to deliver high value care, but change needs to be driven by evidence based policy and investment, argue Jessica Watson and colleagues